High-Throughput Identification of Antibacterials Against Pseudomonas aeruginosa - Li, Shijia; She, Pengfei; Zhou, Linying; Zeng, Xianghai; Xu, Lanlan; Liu, Yaqian; Chen, Lihua; Wu, Yong (Frontiers in Microbiology, 2020)
Antibiotic resistance is a growing public health concern, though the constant development of new antibiotics. The combination of high-throughput screening and drug repurposing is an effective method for developing new therapeutic uses of drugs. In the present study, we have screened a drug library consisting of 1,973 off-patent drugs already approved by the Food and Drug Administration and 903 drugs from the natural product library, to identify antimicrobials against Pseudomonas aeruginosa. Using a microtiter plate-based high-throughput screening assay, we screened 39 drugs that inhibit P. aeruginosa planktonic or biofilm formation. Among these, most of the drugs are antibiotics. Phenotype analysis was used to further evaluate the antibacterial activities of these drugs. Further investigation showed that the combined therapy of tetracycline antibiotics demeclocycline hydrochloride (DMCT) and the novel antimicrobial peptide SAAP-148 showed effectively synergistic antimicrobial effects against P. aeruginosa PAO1. Time-kill curve assay and murine models of cutaneous abscesses further confirmed the synergistic effect. In addition, the combination of DMCT and SAAP-148 had the potential against clinical isolated strains of multi-drug resistant (MDR) P. aeruginosa. Our results clearly indicate that DMCT and SAAP-148 combined therapy could be an effective approach in combating multidrug resistant P. aeruginosa related infections.